Exploratory effects of a mindfulness+lifestyle program for type 2 diabetes prevention on parental psychosocial adjustment in families of Latino adolescents - Daniels, Raquel, author; Shomaker, Lauren, advisor; Bellows, Laura, committee member; Ortega, Lilyana, committee member (Colorado State University. Libraries, 2020)
Latino adolescents have a particularly high risk of developing youth-onset type 2 diabetes (T2D) compared to other racial/ethnic groups. Latino families frequently experience high levels of stress due to a variety of social/environmental factors including stigma, discrimination, immigration, and acculturation. Culturally adapted, family-based intervention programs designed specifically for Latino adolescents to increase healthy eating and physical activity show strong potential to reduce adolescents' risk of T2D. Yet, existing programs rarely address the heightened psychological stress faced by Latino families, which is likely to interfere with making lifestyle changes. It is possible that the integration of mindfulness-based training into a culturally-adapted, family-based lifestyle program will result in more favorable family functioning and parental psychosocial adjustment than a lifestyle program alone. The current thesis project was a secondary data analysis of a randomized controlled trial designed to pilot a 6-week/12-session culturally-adapted, family-based lifestyle intervention, with and without a mindfulness-based training component, in N = 18 Latino families with adolescents at risk for T2D. The aims were to explore the comparative effectiveness of the mindfulness+lifestyle intervention, versus lifestyle only, on parent psychosocial adjustment and to characterize to what extent changes in parent psychosocial adjustment corresponded to changes in adolescents' own psychosocial adjustment and degree of risk for T2D. At baseline, immediate post-intervention, and six-months follow-up, parents completed validated survey measures of parent perceived stress and parent depression symptoms. Family functioning also was assessed at baseline. At all intervals, adolescents self-reported their levels of perceived stress and depression symptoms, and adolescent risk for T2D was determined from body mass index (BMI) metrics, insulin resistance, and fasting glucose. The analytic plan included analyses of covariance (ANCOVA) as well as a reliable change index. Correlations were used to describe simple correspondence between parent and adolescent characteristics. ANCOVA results indicated that changes in parent depression/stress at post-intervention and six-month follow-up not differ by intervention. Reliable change analyses revealed that one parent from each condition experienced a reliable change decrease in perceived stress and one parent from the lifestyle only condition experienced a reliable change decrease in depressive symptoms. In correlation analyses, greater decreases in parent depression symptoms were correlated with greater decreases in adolescent perceived stress at post-intervention, and this association was apparent in the mindfulness+lifestyle condition as opposed to lifestyle only. Also in mindfulness+lifestyle only, higher baseline family chaos and baseline parental depressive symptoms were correlated with greater decreases in adolescents' insulin resistance. These highly exploratory findings require follow-up in a larger, adequately powered trial, but suggest the possibility that family and parental psychosocial characteristics relate to health outcomes in adolescents at-risk for T2D among Latino families taking part in mindfulness+lifestyle programming. Consistent with a selective or indicated prevention framework, families with more psychosocial difficulties may stand to benefit the most from integrative health interventions.
Keywords: culturally-adapted; Latino; type 2 diabetes; family functioning; adolescent; Latino families